2014
DOI: 10.1002/ajh.23837
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol increases the bone marrow hematopoietic stem and progenitor cell capacity

Abstract: Resveratrol is a plant-derived polyphenol that has shown protective effects against many disorders including, several types of cancers and other age-associated diseases as well as blood disorders in cultured cells and/or animal models. However, whether resveratrol has any impact specifically on normal blood stem cells remains unknown. Here we show that a three-week treatment of resveratrol increases the frequency and total numbers of normal bone marrow hematopoietic stem cells (HSC) without any impact on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…However, the role of RES/SIRT1 on different cells remains controversial. Some studies demonstrated that RES could enhance cell survival, proliferation and multi-potent progenitor capacity, prevent senescence in cultured primary human keratinocytes, bone marrow cells and other cell types ( Ido et al, 2015 ; Rimmele et al, 2014 ). Whereas, some other evidences showed that RES could trigger cell cycle arrest, apoptosis, senescence and inhibit proliferation of cancer cells ( Jackson et al, 2016 ; Zhu et al, 2015 ) and vascular smooth muscle cells ( Guo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of RES/SIRT1 on different cells remains controversial. Some studies demonstrated that RES could enhance cell survival, proliferation and multi-potent progenitor capacity, prevent senescence in cultured primary human keratinocytes, bone marrow cells and other cell types ( Ido et al, 2015 ; Rimmele et al, 2014 ). Whereas, some other evidences showed that RES could trigger cell cycle arrest, apoptosis, senescence and inhibit proliferation of cancer cells ( Jackson et al, 2016 ; Zhu et al, 2015 ) and vascular smooth muscle cells ( Guo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other dietary compounds that have been reported to have effects on hematopoiesis include resveratrol and curcumin. Resveratrol is a naturally occurring plant-derived polyphenol and resveratrol treatment increased bone marrow HSPCs [76] as well as protected HSCs from radiation induced injury [77]. Curcumin treatment in vitro induced apoptosis in leukocytes from JAK2 V617F positive MPN patients [78].…”
Section: Dietmentioning
confidence: 99%
“…Resveratrol was shown, for example, to bind several receptors involved in hematopoiesis, including aryl hydrocarbon receptor and integrin αvβ3, both of which have been linked to HSC activity [24–26]. Furthermore, application of resveratrol via the food was able to partially restore the hematopoietic defect in vivo in a Fancd2 knockout mouse model [27], and it was shown that in vivo treatment of mice with resveratrol resulted in an increase of HSC numbers [28]. Moreover, resveratrol has been shown to inhibit cellular oxidative stress, endoplasmic reticulum stress, and lipid raft perturbation [29, 30].…”
Section: Introductionmentioning
confidence: 99%